O impacto da presença de sistemas de cromossomos sexuais múltiplos na diferenciação genética: a família Erythrinidae (Teleostei, Characiformes) como modelo - Souza, Fernando Henrique Santos de (Universidade Federal de São Carlos, 2022)
The biodiversity of the Neotropics remains poorly understood, and although allopatry is one of the main factors that promote speciation, chromosomal rearrangements and the evolution of sex chromosomes can also play important roles. Chromosomal rearrangements involving sex chromosomes have the potential to reduce introgression events and facilitate reproductive isolation. Thus, the objective of this work was to analyze the influence of allopatry, chromosomal rearrangements and the presence of multiple sex chromosome systems on the genetic diversification of the Neotropical fish species Hoplias malabaricus and Erythrinus erythrinus through cytogenetic and genomic analyses. We analyzed sympatric and allopatric populations that differ by i) chromosomal characteristics (named karyomorphs), ii) sympatric versus allopatric distributions, and iii) presence and absence of heteromorphic sex chromosomes. Altogether, 10 localities of H. malabaricus were analyzed that presented six distinct karyomorphs and three localities of E. erythrinus with two distinct karyomorphs. The different karyomorphs showed variations both in the number of chromosomes and in the presence or absence of multiple sex chromosome systems. The results indicated that although karyomorphs represent genetically divergent groups, they can be better understood when analyzed in conjunction with their geographic distribution and environmental conditions. The multiple X1X2Y sex chromosome system, present in one of the karyomorphs of both species, was associated with greater interpopulation genetic differentiation compared to the effect of allopatry. For H. malabaricus, the presence of such a multiple system may have contributed to levels of genetic differentiation between karyomorphs A and D in syntopy equivalent to the levels of differentiation of allopatric populations of karyomorph A. In general, the results for both species suggest that the presence of neo sex chromosome systems may have contributed to the emergence and fixation of interpopulational differences, which may have contributed significantly to the emergence and fixation of reproductive isolation. Thus, one of the hypotheses is that the occurrence of chromosomal rearrangements, especially those related to sex chromosomes, may have accelerated the speciation process for these species and amplified the differentiation resulting from allopatry.
The impact of the presence of a multiple sex chromosomes system in the genetic differentiation: Erythrinidade family (Teleostei, Characiforms) as model
Keywords: Diversidade genética; Peixes; Cromossomos sexuais; DArTSeq; Evolution; Genetic diversity; Fish; Sex chromosomes; CIENCIAS BIOLOGICAS::GENETICA